(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study aimed to analyze the scientific productivity of Arthropathy research from 2010 to 2020 with an international outlook. The primary purpose of the study is to understand how far the Arthropathy research literature in the state of the art while it comes as a lifestyle disease. The data retrieved from the WoS database; take a sum of 4221 records contributed by 23083 authors. The overall study period finds that PEI value is increasing trend from 2017 to 2020. The degree of collaboration over the years from 2010-2020 and varies from 0.91 to 0.97. The mean value is 0.938. “Wukich DK is the highest H index value 13 (17 Records). Lotka’s law tested our study P-Value, then it is founded that the value of the observed authors was higher than that of the expected value which is 5.780324. To apply Price Square Root Law in study √N =151(7.09%), half of the literature 299.26, but it turned that it is not applicable in the study. The year 2020 shows the topmost value in CI (5.79), CC (0.185) and MCC (0.7210). The research ensures the current state of Arthropathy research and literature. It should provide new insights into future development in the varied sub-disciplines of Arthropathy.